Problems of the psychoanalytic direction of mental development as the formation of personality. - Zunnunova Nozima Mahkamboy qizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The main idea of ​​depth psychology (psychoanalysis) is - Unconscious aspirations serve as the force that stimulates and directs the development process. Since this energy is innate, development is considered, in fact, as self-development, the transformation of those drives that are naturally inherent in a person (aggression, libido, anxiety, feelings of inferiority) and are not recognized by him. Also in these theories, we can see the first attempts to create an age periodization.